Multispectral photonic jet shaping and steering by control of tangential electric field component on cuboid particle - Liu Cheng-Yang; Chen Weiyu; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2021, 2021)
Title screen